Números primos: propriedades, aplicações e avanços - Morimoto, Ricardo Minoru [UNESP] (2014)
Prime numbers have been studied for millennia and still hide many mysteries. The focus of this work is on prime numbers. We present some properties, special primes, recent advances and some primality tests that detect if a number is prime or composite